2013
DOI: 10.3390/ijms140816532
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Lin28-Mediated miRNA and mRNA Regulation—A Structural and Functional Perspective

Abstract: Lin28 is an essential RNA-binding protein that is ubiquitously expressed in embryonic stem cells. Its physiological function has been linked to the regulation of differentiation, development, and oncogenesis as well as glucose metabolism. Lin28 mediates these pleiotropic functions by inhibiting let-7 miRNA biogenesis and by modulating the translation of target mRNAs. Both activities strongly depend on Lin28’s RNA-binding domains (RBDs), an N-terminal cold-shock domain (CSD) and a C-terminal Zn-knuckle domain (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 90 publications
5
101
0
1
Order By: Relevance
“…Accordingly, a number of genetic pathways have been discovered in which LIN28 influences development via its regulation of let-7. The molecular aspects of the LIN28/let-7 axis have been studied in exquisite detail (Loughlin et al, 2012;Mayr and Heinemann, 2013;Nam et al, 2011). In brief, studies have shown that LIN28 can bind to both pri-and pre-let-7 in vivo and block their processing (Fig.…”
Section: Molecular Mechanisms Of Lin28 Action: Two Separate Mechanistmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, a number of genetic pathways have been discovered in which LIN28 influences development via its regulation of let-7. The molecular aspects of the LIN28/let-7 axis have been studied in exquisite detail (Loughlin et al, 2012;Mayr and Heinemann, 2013;Nam et al, 2011). In brief, studies have shown that LIN28 can bind to both pri-and pre-let-7 in vivo and block their processing (Fig.…”
Section: Molecular Mechanisms Of Lin28 Action: Two Separate Mechanistmentioning
confidence: 99%
“…Once oligo-uridylated, pre-let-7 is more rapidly degraded than unmodified pre-let-7 (Heo et al, 2008), and it has been shown that, in mouse ESCs, the 3′-5′ exonuclease DIS3L12 catalyzes the decay of oligo-uridylated pre-let-7 . For a recent, in-depth review of LIN28-mediated control of let-7, the reader is referred to Mayr and Heinemann (2013).…”
Section: Molecular Mechanisms Of Lin28 Action: Two Separate Mechanistmentioning
confidence: 99%
“…30,31 Recent studies simultaneously showed that miR-let-7 was mainly regulated by LIN28, an important RNA binding protein, targeting prelet-7 to block its maturity, thus facilitating carcinogenesis. [32][33][34] Meanwhile, Chaulk et al 35 recently showed that YAP1 successfully decreased mature let-7 expression by regulating the LIN28/Let-7 axis in breast cancer cell lines. Interestingly, YAP1 inhibition did not decrease mRNA expression of LIN28 but markedly decreased LIN28 protein expression, indicating that YAP1 may regulate LIN28 through post-transcriptional events, therefore, to reduce mature let-7 expression with no effect on pre-let-7.…”
Section: Discussionmentioning
confidence: 99%
“…Интересно отметить, что удаление кластера генов микроРНК-17-92 приводит к увеличе-нию экспрессии другого кластера генов микро РНК-106b-25, также избирательно экспрессирующегося в не-дифференцированных спермато гониях, что, по всей видимости, указывает на их функциональное сотруд-ничество [68]. Показано, что при дифференцировке сперматогониев снижается регуляция семейством микроРНК let-7 таргетных целей мРНК Mycn, Ccnd1 и Colla2 [69][70][71][72][73][74][75].…”
Section: этапы сперматогенезаunclassified